Perinatal mental health policy : young women's mental health support during pregnancy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Social Policy at Massey University - Parsons, Jane Elizabeth (Massey University, 2008)
A woman's reproductive period is when she is most likely to suffer mental ill-health with this risk increased for young women. Mental ill-health in the perinatal period is identified as common but with significant implications for the young women and her family (Dearman et al., 2007; Petrillo et al., 2005; Riecher-RÖssler & Steiner, 2005). From as early as a few weeks post conception, the foetal brain is found to be affected by maternal stress and mental ill-health. This continues to affect the infant postnatally and is exacerbated if maternal mental ill-health is not treated. Young women are more likely to experience impediments to their wellbeing in the perinatal period. Thus, introduction of suitable formal support perinatally can have a prophylactic effect on maternal and infant mental illness. Through feminist research methods, utilising semi-structured qualitative interviews, four pregnant women thirty years and under in the perinatal stage of pregnancy and four health professionals working in the field of maternal mental health explore with the researcher their experiences of mental health support and education during pregnancy. This research demonstrates how services are currently unable to appropriately meet the needs of young pregnant women due to lack of attention to gender and youth issues and the dominance of a medical model understanding that has allowed this negation through minimising holistic, contextual treatment. The gendered construction of health services and recent market principles in state provisions are evidenced by the compartmentalisation of services, lack of collaboration between these services, competition for resources, and rigidly defined roles of health professionals that present access barriers for young pregnant women. A need to enhance formal supports and create policy frameworks and practice guidelines to direct this support is identified alongside recommendations for increased service provision, education, and screening at the primary healthcare level.
Keywords: New Zealand; Maternal health services; Prenatal care; Mental health policy; Pregnant women -- Mental health; Young women -- Health and hygiene